2014
DOI: 10.1167/iovs.14-14017
|View full text |Cite
|
Sign up to set email alerts
|

Translation, Cultural Adaptation, and Rasch Analysis of the Visual Function (VF-14) Questionnaire

Abstract: The Chinese translated VF-14, VF-11R, and VF-8R were valid and could be applied to assess cataract outcomes in Chinese settings. The existing shorter version had good agreement with the new Chinese version, which signifies that there was no need to develop a different version of the VF-14 in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 44 publications
1
36
0
1
Order By: Relevance
“…All items showed values inside the interval considered productive for measurement. 13,17 Only the infit and outfit of item 1 were outside the more stringent criterion (0.7-1.3) proposed by Pesudovs et al 16 and Khadka et al 14…”
Section: Item Fit Statisticsmentioning
confidence: 91%
See 2 more Smart Citations
“…All items showed values inside the interval considered productive for measurement. 13,17 Only the infit and outfit of item 1 were outside the more stringent criterion (0.7-1.3) proposed by Pesudovs et al 16 and Khadka et al 14…”
Section: Item Fit Statisticsmentioning
confidence: 91%
“…Disordering of categories occurs when the response options do not follow expected hierarchical ordering. 13,22…”
Section: Rating Scale Structurementioning
confidence: 99%
See 1 more Smart Citation
“…7,16 Similar to this study, a high percentage of missing data on driving items was reported in other studies conducted in China. 17,18 Unlike in western countries, driving is not common in China, especially in the elderly population. Hence, the relevance of the driving items is questionable.…”
Section: Discussionmentioning
confidence: 99%
“…11 When compared to all of the existing translated and validated cataract-specific instruments in China (the Visual Function Index-14, targeting = -0.83; Catquest, targeting = 0.50; National Eye Institute Visual Functioning Questionnaire, targeting = -1.25), the HKQ demonstrated much better targeting in fact had a near perfect (item and person mean difference = -0.05) targeting. 16,17,20 This is probably because the HKQ items were specifically developed for Chinese people. This demonstrates the significance of population-specific content development in the performance of an instrument.…”
Section: Discussionmentioning
confidence: 99%